Relationship among Iranian EFL students’ foreign language anxiety, foreign language listening anxiety and their listening comprehension. - Serraj, Samaneh; Noordin, Noreen (Canadian Center of Science and Education, 2013)
Anxiety is an influential factor in a foreign language learning domain and plays a crucial role in language learners’ performance. The following study was conducted to explore the possible impact of Foreign Language Anxiety and Foreign Language Listening Anxiety on language learners’ listening skill. The researcher was interested to know the correlation that could exist among the three variables: Listening Comprehension, Foreign Language Anxiety and Foreign Language Listening Anxiety. The participants of the study were 210 Iranian EFL students in Iran. The study revealed that there was -.414 correlations between FLLA and listening comprehension and -.214 correlations between FLA and listening comprehension whereas FLA and FLLA enjoyed a .513 correlation. It can be concluded that the relationship between Foreign Language Anxiety and Foreign Language Listening Anxiety of the participants are in accordance with each other. Furthermore the result shows that the impact of FLLA on Iranian students’ listening comprehension skill is significantly more problematic. Therefore it is recommended that FL teachers and learners should be more aware of the hindering effect of FLA and FLLA in particular on the process of teaching and learning the listening comprehension.